ANALISIS BIMBINGAN WAWASAN KARIR DI SEKOLAH DASAR: STUDI KUALITATIF DI SD GMIT 33 MORU 01 - Onarita Lanoni; Naomi Karpada, Paulus Animau, Yessy Mata, Petrus Mau Tellu Dony, Yermias Samuel Wabang (CV. ADIBA AISHA AMIRA (ADISAM PUBLISHER), 2025)
The development of career development in SD Geme 15 Morn Abad, Alor Regency, the research method used is a qualitative method with direct interviews, with the homeroom teacher of class 6. The results of the study show that career development in SD Gmit 33Moru 01 is developing well and running according to the curriculum, This research is expected to serve as a reference in efforts to develop career insight in elementary schools. Furthermore, this research also reveals various challenges in developing career insight in elementary schools. Therefore, collaborative efforts between the community and government schools are essential to maintain the sustainability of career development as a subject in elementary schools. Career development is an ongoing process involving the planning, implementation, and evaluation of an individual's career goals. In the context of an ever-evolving workplace, insight into career development is crucial to help individuals understand their potential, identify opportunities, and develop relevant skills. This article discusses the importance of career development insights in enhancing work readiness, intrinsic motivation, and adaptability Industry change. With an integrated approach between education, training, and career guidance, individuals can design career paths that align with their interests, values, and competencies. A deep understanding of the dynamics of the workplace and mastery of soft and hard skills are also supporting factors in achieving long-term career goals.